(untitled) (Marketing Journal, 2026)
This article explores the evaluation of Return on Marketing Investment (ROMI) in B2B distribution companies. It examines the unique challenges of attributing marketing impact in multi -touch, long -sales -cycle environments, and highlights methodologies for c alculating ROMI at campaign, channel, and strategic levels. Emphasis is placed on integrated data infrastructure, analytical modeling, and cross - functional governance to optimize marketing spend, improve decision -making, and transform marketing from a cost center into a value driver. Practical examples and a maturity model illustrate implementation strategies.